STUDY OF FUZZY MODELLING ON ELECTRICAL DISCHARGE MACHINING (EDM) OF TOOL DIE STEEL (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Estimating the performance becomes necessary in today’s modern world in order to reduce the number of experiments in precision manufacturing, especially in electrical discharge machining (EDM). Hence, in the present investigation fuzzy-based algorithm using MATLAB software for prediction of Material Removal Rate (MRR), Tool Wear Rate (TWR), and Surface Roughness (SR) in the EDM processes. The discharge current, pulse duration, and pulse-off time are selected as input variables and the responses like MRR, TWR, and SR are estimated. The proposed fuzzy model developed in this study provides a more precise and easy selection of any EDM input parameters for the required responses which leads to better machining conditions and decreases the machining costs. Observations indicate that the fuzzy modeling results of EDM were in good agreement with experimental findings demonstrating 90% predictions can be achieved.